Profil Metakognitif Siswa Dalam Pemecahan Masalah Prisma Dan Limas - Muliawati, Lelly Rizkyta; , Masduki, S.Si, M.Si (2016)
This research aimed to describe the profile of student's metacognitive skills in solving problems prism and pyramid. This research is a qualitative descriptive. Subjects of this study is 6 students taken from class VIII H at SMP Negeri 1 Gatak. The data collection technique using the test method, interviews, observation and documentation. Data analysis technique conducted in three stages of data reduction, exposure data, and conclusions or verification. The analysis was developed based on three categories are planing, monitoring and evaluating are students who have the math skills of high , medium and low. The result showed that students who have high math ability, will have good metacognitive skills in problem solving prism and pyramid. Students who have medium math ability, have metacognitive skills were average . While students who have low math ability, less able to use metacognitive skills in solving problems.